Dry anaerobic digestion of the fine particle fraction of mechanically-sorted organic fraction of municipal solid waste in laboratory and pilot reactor. (December 2021) - Basinas, Panagiotis; Rusín, Jiří; Chamrádová, Kateřina
Highlights: Digestion of the small particle size fraction of municipal waste was investigated. Non-biodegradable molecules limited methane generation potential of substrate. The absence of unreacted layer favoured degradation of more organics of waste. Better mixing of substrate and microorganisms promoted methane generation. Digestate of pilot reactor presented low stability and high heavy metal content. Abstract: High-solid anaerobic digestion of the very small particle fraction of mechanically-sorted organic fraction of municipal solid waste (OFMSW) was examined in mesophilic digestion tests in a conventional laboratory (0.013 m 3 ) and a pilot (0.300 m 3 ) reactor. The non-biodegradable and recalcitrant molecules together with the low protein and starch contents of the small-particles of OFMSW limited the methane generation potential of substrate. In the conventional AD system, methane yields remained low at 0.139 m 3 kgVS -1 due to formation of a non-reacting layer on digestate surface, which restricted utilization of the available in OFMSW digestible organics. The absence of surface solid crust in the pilot unit favoured consumption of a greater proportion of volatile solids of the OFMSW. Dry AD was remarkably stable over the entire period and negligibly effected by the toxic H2 S yields. Methane generation (0.167 m 3 kgVS -1 ) was increased 1.2-fold compared to the conventional system due to a better mixing of substrate and microorganisms achieved inside the pilot reactor, which led to an increase of the digested volatile organics. Digestate presented low stability and high heavy metal content, both of which restrain its implementation as soil conditioner or fertilizer in agriculture. A secondary co-digestion treatment may be required for the neutralization of digestate.